Course of social support and associations with distress after partial laryngectomy. Issue 3 (27th April 2022) - Roick, Julia; Dietz, Andreas; Koscielny, Sven; Pabst, Friedemann; Breitenstein, Kerstin; Oeken, Jens; Schock, Elke-Juliane; Boehm, Andreas; Winter, Iwona; Büntzel, Jens; Müller, Andreas; Plontke, Stefan K.; et al.
Abstract: Purpose: Social support has been shown to be positively associated with quality of life and adjustment after a cancer diagnosis. The present study investigates the course of social support up to one year after partial laryngectomy and its association with distress. Design: Longitudinal questionnaire study. Sample: A total of 428 patients after partial laryngectomy (mean age: 64, SD = 11, 91% male). Methods: Patients completed questionnaires before treatment (t1), one week after a partial laryngectomy (t2), 3 months (t3), and one year (t4) thereafter. Social support was evaluated at t2, t3, and t4 using a brief version of the Social Support Questionnaire. Distress was measured at t2, t3, and t4 using the HADS. Descriptive statistics for social support were computed across the three measurement points. Changes were analyzed by Wilcoxon signed-rank tests. Associations with distress were identified using linear regression analyses. Findings: Social support increased between t2 and t3 and decreased to baseline level between t3 and t4. Distress at t2 was associated with social support at t2 (B = −0.15, p < 0.01) and distress at t3 with social support at t3 (B = −0.19, p < 0.01). Distress at t4 was related to social support at t2 (B = −0.10, p = 0.05). Conclusions: Although perceived social support increases after partial laryngectomy, it decreases again during the course of aftercare. Implications for Psychosocial Providers or Policy: Social support resources should be assessed to identify patients at risk for worse psychological well-being.